THE ROLE OF BUDGET PARTICIPATION IN ENHANCING MANAGERIAL PERFORMANCE OF LOCAL GOVERNMENT AGENCIES MEDIATED BY JOB SATISFACTION - Irianto, Okto; Manuhutu, Fenty Yoseph; Mattulada, Andi; Muliati, Muliati; Jamaluddin, Jamaluddin; Usman, Ernawaty; Usman, Rudy (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
Despite extensive research on budget participation and managerial performance, critical gaps remain regarding the psychological mechanisms through which participation influences performance, particularly in public sector contexts where fiscal decentralization is formal rather than operational. This issue is especially pronounced in Indonesian Special Autonomy regions, where substantial fiscal transfers coexist with persistent performance and accountability challenges. This study investigates whether behavioral engagement mechanisms or structural fiscal arrangements play a more decisive role in shaping managerial performance in Merauke Regency, South Papua. Using cross-sectional survey data from 346 structural officials across 26 government agencies and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM), the results show that budget participation significantly enhances job satisfaction (β = 0.326, p < 0.001) and managerial performance (β = 0.554, p < 0.001). Job satisfaction partially mediates this relationship, accounting for 21% of the total effect. In contrast, fiscal decentralization exhibits no significant effect on either job satisfaction or managerial performance. These findings highlight that, within transitional governance and Special Autonomy contexts, behavioral mechanisms embedded in participatory processes exert stronger influence on performance than formal structural decentralization. By demonstrating the limited effectiveness of fiscal decentralization in the absence of genuine operational autonomy, this study extends goal-setting theory and the two-factor theory to underexplored public-sector contexts. It provides policy-relevant insights for improving governance performance beyond structural reform alone.